Analisis Titik Impas Usahatani Padi Sawah di Desa Lamolori Kecamatan Lamolori Kabupaten Konawe Selatan - Gusti Ayu Putu Ariani; Sitti Aida Adha Taridala; Abdi Abdi (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This study aims to determine the amount of income in lowland rice farming in Lamolori Village, Mowila District and to determine the break-even point that occurs in lowland rice farming in Lamolori Village, Mowila District. The research was carried out in July-Agustust  2021. The data to be taken is the 2021  planting season data. The population in this study is 25 people of lowland rice farmers. The number o samples was determined using a non-probability sampling technique with saturated samplig or sensur sampling methods. The variables of this research are the age  o the farmer, the volume of lowland rice production, revenue, selling price and costs. The costs taken  into account are variable costs and fixed costs. The analytical  to used is Break Even Point  by calculating income, revenue and costs incurred by farmers. The results show that: (1) The amount of income  in lowland  rice farming per  hectare per planting season in Lamolori Village, Mowila  District is IDR 2,543, 594 and (2) The break-even point in lowland rice farming per hectare per growing season in Lamolori Village, Mowila Districtis as follows: sales value (BEP np) is IDR 2,706,716, prodaction volume break-even point (BEP vp) is 601,49 kilograms, point the break-even area of land (BEP LL) is 2 hectares and the break-even point of the  price of dry grain harvested per hectare per planting season  in Lamolori Village, Mowila District is IDR 2,793.60.